Evolusi Corak Dan Madzhab Tafsir: Kajian Historis Epistimologis - Wilda Afasari (Program Pascasarjana IIQ Jakarta, 2025)
This study analyzes the development of Qur'anic interpretation from historical and epistemological aspects to understand the dynamics of interpretive approaches in various contexts of the era. The main problem raised is the lack of integration between historical and epistemological analysis in previous studies, which often separate the two. This study uses historical methods to trace the chronology of the development of interpretation and epistemological analysis methods to examine the scientific basis behind various types of interpretation, such as fiqh, philosophical, Sufi, and literary interpretations. The results of the study show that the development of interpretation is influenced by the social, political, and cultural contexts in each era, with variations in methodological approaches in each school of thought that reflect the flexibility of interpretation. This study also found that cross-school dialogue and the use of modern technology provide opportunities to produce interpretations that are more relevant to the challenges of the times. In conclusion, the integration between historical and epistemological analysis is important to provide a more comprehensive understanding of Qur'anic interpretation. This study recommends further exploration in the use of digital technology and strengthening cross-school dialogue to support the development of inclusive and adaptive interpretations to contemporary issues.